The evaluation of the nutritional habits of 14-25 years old people with skin problems - Sökülmez Kaya, Pınar; Asal Ulus, Canan; Taşcı, Bahtinur (Progress in Nutrition, 2020)
Objective: To investigate the nutritional habits of the 14-25 years old people with skin problems.Design: We performed a cross-sectional study with random sampling of participants. Skin problems wasquestioned with questionnaire form. Last three days food consumption was recorded and food consumptionfrequencies were questioned. Also anthropometric measurements were taken. Setting: A state university andtwo high school in Samsun, Turkey. Subjects: Students (n =400 ) aged between 14-25 years. Results: Amongstudents, 251 were women and 149 men. 219 of them have skin problems and 181 didn’t have any skinproblems. Mean BMI (body mass index) of students was 20.95±2.67 kg/ in women and 22.65±3.17 kg/ inmen. Mean body mass index in students with skin problem (SP) was 21.55 ± 2.91 kg/m2 and without SP was21.61±3.07 kg/. Among students who have SP problems (n = 219), acne (35.2%) was the first skin problem.Gender, sleep duration, physical activity, frequency of eating out, consumption of tea with food, french friesconsumption, daily water intake amount had a significant difference on skin problems (p